Fatigue Strength Determination of AISI 316L Steel and Welded Specimens Using Energy Methods - Danilo D’Andrea; Giacomo Risitano; Pasqualino Corigliano; Davide D’Andrea (Engineering Proceedings, 2025)
AISI 316 is a stainless steel known for its exceptional corrosion resistance and excellent mechanical properties. It is used in the chemical and pharmaceutical industries, food processing equipment, and medical devices. This alloy’s wide range of applications underscores its importance in industries requiring materials that can withstand extreme conditions while maintaining structural integrity and performance. Additionally, the excellent weldability and formability of AISI 316 allow for versatile design and production processes, ensuring durable and reliable performance in marine environments. This work aims to examine the behavior of AISI 316L and its welded joints under high-cycle fatigue loadings using infrared thermography (IR). Two kinds of experimental tests are performed on specimens with the same geometry: static tests and stepwise succession tests. The results of the static tests are in accordance with the stepwise succession test results in predicting the fatigue properties.